Performance Analysis of Parabolic trough Concentrating Photovoltaic Thermal System. (2016) - Manokar, A. Muthu; Winston, D. Prince; Vimala, M.
Abstract: The electricity and heat produced simultaneously in a photovoltaic thermal (PVT) system from solar energy is about 60-70% efficient. The traditional photovoltaic (PV) system conversion of electricity from solar energy is only about 6-15% efficient, whereas 85% of the incoming solar energy is either reflected or absorbed as heat energy, which are cooled by water or air coolant to utilize the all incoming solar energy on system. The main objectives in this project work is combining two systems; Parabolic Trough as a concentrator and channel PV/T collector as a receiver. The performance study of Parabolic Trough Concentrating PVT is done and evaluated through water flow with concentrating PVT.